The motivational role of feedback in motor learning: Evidence, interpretations, and implications - Chiviacowsky, S. (Advances in mental skills training, 2021)
In this chapter, four lines of behavioral research showing the motivational impact of feedback on motor learning developed over the past 20 years were reviewed. Consistent with theoretical expectations (Ryan & Deci, 2000), the reviewed findings indicate that positive motivational effects of feedback are mediated by the satisfaction of learners` basic psychological needs, with studies performed to date predominantly confirming the competence and autonomy needs. Higher feelings of autonomy and enhanced perceived competence or expectations of future successful performance have been suggested to trigger dopaminergic responses that enhance memory consolidation and neural pathway development, as well as to strengthen the coupling of goals to actions at several different levels, thus optimizing motor learning (Wulf & Lewthwaite, 2016). Future research on the motivational impact of feedback in motor learning can not only generalize the findings to different settings (e.g., dance, music, sports, martial arts, physical therapy, medical skills) and populations, but also follow many directions and levels of analysis. For example, research has been developed that mainly observes the impact on learners` competence and autonomy psychological needs. Still lacking experimentation is the potential importance of relatedness-supportive feedback in motor skill acquisition. Social relatedness has been observed to affect motor learning when manipulated through instructions (e.g., Gonzalez & Chiviacowsky, 2018), with positive learning outcomes detected when learners felt genuinely liked, connected, and respected during practice. Thus, feedback provided in a way that emphasizes acknowledgment, caring, and interest in participants` experiences may potentially result in higher motivation and learning relative to feedback disregarding learners` satisfaction of the relatedness need. It is also worth noting that the reviewed findings involved learning mainly at an individual level, with participants practicing the task alone, while motor skill learning is often taught in groups or teams. Hence, further studies could focus on how individuals collaboratively sharing the acquisition of a motor skill in groups may be affected by motivational feedback. The application of neuroscience methods may also help to identify the neural underpinnings of motivational states resulting from feedback manipulation (e.g., Reeve & Lee, 2019). These findings have applicability in multiple learning settings. As reviewed, the way in which feedback is handled during practice can substantially affect the learning process. Increased motivation and positive effects on learning can be expected when feedback affords opportunities for learners to experience feelings of success and efficacy, supports learners` need for autonomy and competence by allowing choices over the feedback delivery, helps learners to be aware of self-improvements over time through evaluative comparative feedback, and highlights a learnable view of skills or conception of ability. Contrarily, practice conditions in which feedback emphasizes greater errors or mistakes, in which the learner is never allowed to exercise control over the feedback provision, in which feedback does not highlight improvements over time, and which induce an entity or fixed view of skills most certainly decrease learners` motivation and impair learning. Observing the interplay between motivational feedback research and real-world learning settings may allow more efficient practice methods to be designed, thus answering several specific problems in intervention (e.g., Winstein, Lewthwaite, Blanton, Wolf, & Wishart, 2014). Understanding how the type, content, and meaning of feedback can influence motivation and learning may allow professionals in many contexts to develop more effective learning environments.